Approaches to “mental health” in low-income countries: a case study of Uganda - Shaw, Ian; Middleton, Hugh (Emerald, 2013)
Purpose – The purpose of this paper is to explore the ways in which “mental health” difficulties are approached in low-income countries, using a case study of Uganda focus down upon the issues.